Evaluation of maize (Zea mays L.) hybrids for growth, yield and yield attributing traits in Rampur, Chitwan, Nepal - Dhakal, Krishna Hari (Journal of Agriculture and Natural Resources, 2025)
Hybrid maize plays a crucial role in enhancing maize productivity in Nepal due to its higher yield potential and superior agronomic performance compared with open-pollinated varieties. The objective of this study was to identify high-yielding maize hybrids suitable for winter planting under the Terai conditions of Nepal. A total of ten maize hybrids were evaluated in a randomized complete block design with three replications during the winter season of 2024-25 at Rampur, Chitwan. The results revealed significant differences (p